Self learning kits to develop five comprehension skills among freshmen college readers in vocational schools - Arcaya, Francisca Mata 1949- (1980)
The self learning kits (SLK) presented in this study aims to help individualize the teaching-learning processess. The modular materials aim to develop the skills in getting meaning, noting details, making inferences, getting the main idea, and outlining among freshman college readers in the vocational schools. The selected reading materials for the modules used the Dale-Chall formula. After constructing the modules, the Gates' Reading survey was administered. The study concluded that the use of modules is highly adaptable in fostering comprehension skills in all subject areas. Students learn best if they work with appropriate materials.